Physicochemical, Antioxidant, and Anti-Inflammatory Properties of Rapeseed Lecithin Liposomes Loading a Chia (Salvia hispanica L.) Seed Extract - Ailén Alemán; Selene Pérez-García; Pilar Fernández de Palencia; María Pilar Montero; María del Carmen Gómez-Guillén (MDPI AG, 2021)
Vegetal waste materials were used to produce liposomes with both antioxidant and anti-inflammatory properties. Differences in the chemical composition of rapeseed lecithin (LEC) and a partially purified phospholipid fraction (PPL) were studied in terms of fatty acids (neutral lipids, free fatty acids, and phospholipids), sterols, tocopherols, and amino acid composition. Neutral lipids, campesterol, β-sitosterol, and γ-tocopherol were the most depleted compounds in PPL. Qualitative differences between LEC and PPL were revealed by infrared spectroscopy and differential scanning calorimetry. An ethanol/water antioxidant extract from chia seeds (ChE), with a high content in rosmarinic acid and rosmarinic acid 3-O-glucoside, along with other minor phenolic acids determined by HPLC-MS, was encapsulated in liposomes made of LEC (L-LEC) and PPL (L-PPL) with an entrapment efficiency of 61.3% and 69.3%, respectively. L-PPL suspensions showed smaller particle size and lower ζ potential than their L-LEC counterparts, along with noticeable particle destabilization after 7 days of storage. Antioxidant properties were greater in L-LEC than in L-PPL suspensions. L-LEC, ChE, and lecithin empty liposomes (L-E) showed no cytotoxic effect in either Caco-2 or THP-1 cells and induced downregulation of the inflammation response.